Evaluation of Groundwater Quality in Spring Sources of Bauro Village, Lospalos Administrative Post, Lautém Municipality, Timor-Leste - Juvencio Dos Santos; Listyani Retno; Budiadi Budiadi (Publikasi Indonesia, 2025)
coli and total coliform, during field investigations at several spring locations. The results showed that whereas many spring sources satisfied acceptable drinking water criteria, several sites had higher than average levels of pollutants, underscoring the effects of human activities including inappropriate waste disposal and agricultural runoff. Overall water quality in these springs will be assessed using the Water Quality Index (WQI) standards consist of three core components, as there are three water quality parameters that help to measure the quality of water, which include physical parameters, chemical parameters, and biological parameters. The physical parameters include color, taste, odor, temperature, turbidity, solids, and electrical conductivity. which rated most samples as